The Impact of Return on Equity (ROE) and Earnings Per Share (EPS) on The Stock Price At PT. Ultrajaya Milk Industry and Trading Company, Tbk. - Amalia Nurrohmah; Euis Hernawati (International Journal of Management and Business, 2024)
The aim of this research is to evaluate the impact of return on equity (ROE) and earnings per share (EPS) on the stock price of PT. Ultrajaya Milk Industry and Trading Company, Tbk. This study employs a quantitative methodology. The analysis utilizes secondary data sourced from the company's annual financial reports, specifically focusing on metrics such as return on equity, earnings per share, and stock price over the period spanning from 2017 to 2023. The research included traditional assumption testing and double linear analysis as data analysis methodologies. The findings of this research indicate that the variables return on equity (ROE) and earnings per share (EPS) have a concurrent and substantial impact on the stock price.